Reducing increasing monotonicity of kernels - Rina Ling (International Journal of Mathematics and Mathematical Sciences)
Integral equations with positive increasing kernels are transformed into ones with positive decreasing kernels, and using a similar technique, more positive increasing kernels are reduced to ones with less increasing monotonicity.